Underreporting of Hemorrhagic and Thrombotic Complications of Pharmaceuticals to the U.S. Food and Drug Administration: Empirical Findings for Warfarin, Clopidogrel, Ticlopidine, and Thalidomide from the Southern Network on Adverse Reactions (SONAR) - Moore, Thomas J.; Bennett, Charles L. (Seminars in Thrombosis and Hemostasis, 2012)
The U.S. Food and Drug Administration's (FDA) Adverse Event Reporting System (AERS), familiarly known as “MedWatch,” is the nation's primary tool for postmarket pharmaceutical safety surveillance. This system relies on adverse events voluntarily reported by health care providers and consumers either directly to the FDA or to drug manufacturers, which are required to prepare and forward the information to the agency. Little is known about how frequently adverse events are reported. Previous estimates range from 1 to 31% depending on the event, drug, and time period. We used published incidence studies to calculate reporting rates for hemorrhage, emergency hospitalization, and venous thromboembolism (VTE) associated with four drugs. We estimated annual reporting rates of 1.07% for 33,171 emergency hospitalizations of patients older than 65 years associated with warfarin, 0.9% for 13,363 hospitalizations of clopidogrel and ticlopidine, and 1.02% for an estimated 67,200 hemorrhage cases associated with warfarin. We also estimated a 9-year reporting rate of 2.3% for VTE associated with thalidomide. The incidence of these hematologic adverse drug events is high and reporting rates are low, and near the lower boundary of the 1 to 15% range seen for other events.
Keywords: U.S. Food and Drug Administration; adverse drug events; hemorrhage; venous thromboembolism; warfarin; thalidomide; clopidogrel; ticlopidine